PENGEMBANGAN PROGRAM KEGIATAN PEMBIASAAN BERBASIS TQM DI RAUDHATUL ATHFAL (RA) - Novan Ardy Wiyani (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2017)
This paper is intended to get the steps in the development of habituation activities for young children based TQM in Raudhatul Athfal (RA). There are eight steps in the development of habituation activities for young children based on TQM. First, do a SWOT analysis. Second, make the RA policy that focuses on character building early childhood. Third, formulate a vision, mission, goals, and values that focus on character building early childhood. Fourth, make quality assurance RA graduates. Fifth, determine strategies for achieving quality assurance RA graduates. Sixth, determine the conditioning activity to achieve an indicator on each competency in quality assurance RA graduates. Eighth, perform supervision activities to ensure that the activities of habituation something with SOP.